A Case Study of Non-Violent Property Crime Victimisation in a South African Urban Residential Neighbourhood: Exploring the Excessive Use of Force and Destruction Caused by Burglars to Gain Entry to Victims’ Properties - Graan, Johan van (International Journal of Criminology and Sociology, 2021)
Commentators frequently report on the high prevalence of violent crime in South Africa and often label the country as one of the most violent in the world, with a subculture of violence and criminality. This paper focuses on a different perspective, reporting on the excessive use of force and destruction caused by offenders in South Africa to gain entry to victims’ properties in the execution of non-violent property crimes, in a particular residential burglary. Literature on property crimes has been considering the aggravating circumstances of violent property crimes. However, the use of excessive force and destruction caused by burglars to gain access to victims’ properties in the execution of residential burglary remains relatively untested in the literature. In this light, the purpose of this study is to describe the unprecedented levels of force used and destruction caused by burglars to gain access to victims’ properties during residential burglary victimisation in an urban residential neighbourhood in Johannesburg, South Africa. A qualitative research approach is followed. A case study design was used to select an urban residential neighbourhood in Johannesburg as a case study. A data set of (n = 1 431) crimes were purposively selected by means of non-probability sampling. Qualitative and quantitative content analysis was used to analyse the data. This paper offers valuable insight into the forceful and destructive conduct of burglars in the selected neighbourhood and contributes to the body of knowledge by providing an improved understanding of target hardening as a preventive measure against residential burglary victimisation as well as on methods of entry used by burglars in incidents of residential burglary. The results of reported non-violent property crime victimisation incidences by this community’s neighbourhood watch scheme suggest that residential burglars in the selected neighbourhood are uncharacteristically forceful and ravage in their actions since they frequently revert to extreme use of force and destruction, disproportionate to the crime perpetrated. It is concluded that this radical degree of force used and destruction caused by residential burglars to gain entry to victims’ properties in the execution of non-violent property crimes is not typically associated with residential burglary as compared to countries internationally.